Annealing temperature effects on photoelectrochemical performance of bismuth vanadate thin film photoelectrodes. Issue 51 (16th August 2018) - Shi, Le; Zhuo, Sifei; Abulikemu, Mutalifu; Mettela, Gangaiah; Palaniselvam, Thangavelu; Rasul, Shahid; Tang, Bo; Yan, Buyi; Saleh, Navid B.; Wang, Peng
Abstract : The effects of annealing treatment on crystallization behavior, grain size, electrochemical (EC) and photoelectrochemical (PEC) oxygen evolution reaction (OER) performances of bismuth vanadate (BiVO4 ) thin films are investigated in this work. Abstract : The effects of annealing treatment between 400 °C and 540 °C on crystallization behavior, grain size, electrochemical (EC) and photoelectrochemical (PEC) oxygen evolution reaction (OER) performances of bismuth vanadate (BiVO4 ) thin films are investigated in this work. The results show that higher temperature leads to larger grain size, improved crystallinity, and better crystal orientation for the BiVO4 thin film electrodes. Under air-mass 1.5 global (AM 1.5) solar light illumination, the BiVO4 thin film prepared at a higher annealing temperature (500–540 °C) shows better PEC OER performance. Also, the OER photocurrent density increased from 0.25 mA cm −2 to 1.27 mA cm −2 and that of the oxidation of sulfite, a hole scavenger, increased from 1.39 to 2.53 mA cm −2 for the samples prepared from 400 °C to 540 °C. Open-circuit photovoltage decay (OCPVD) measurement indicates that BiVO4 samples prepared at the higher annealing temperature have less charge recombination and longer electron lifetime. However, the BiVO4 samples prepared at lower annealing temperature have better EC performance in the absence of light illumination and more electrochemically active surface sites, which are negatively related to electrochemical double-layer capacitance ( C dl ). C dl was 0.0074 mF cm −2 at 400 °C and it decreased to 0.0006 mF cm −2 at 540 °C. The OER and sulfide oxidation are carefully compared and these show that the efficiency of charge transport in the bulk ( η bulk ) and on the surface ( η surface ) of the BiVO4 thin film electrode are improved with the increase in the annealing temperature. The mechanism behind the light-condition-dependent role of the annealing treatment is also discussed.